Enhancing higher education experience: The eMadrid initiative at UNED university (2015)
In this paper we focus on the achievements of eMadrid initiative in some fields of technology-enhanced learning, mainly involving the improvement of the mechanisms for open educational content retrieval from Internet, considering Internet resources as potential learning objects. Also we facilitate the integration of remote laboratories and external tools in virtual campuses architectures supporting enriched capabilities and describe a way to cluster and identify learner weaknesses using a learning analytics approach in combination with the item response theory. © 2014 IEEE.